Macroeconomic Determinants of Gold Prices : A Bounds Testing Approach - Singh, Arwinder; Kaur, Navjot (Indian Journal of Finance, 2020)
Despite the demise of gold as a long-standing anchor in the international monetary system, it keeps on alluring its producers, consumers, investors, and speculators over the globe. India is the largest consumer and importer of gold in the world. The investment demand for gold is ascending in India since it is considered as a safe haven. Notwithstanding, high instability in gold prices brings up an issue on its supporting properties. Thus, an attempt was made to identify the macroeconomic determinants of gold prices in India. The study was set to examine the long run as well as short run relationship between gold prices and some macroeconomic variables like BSE Sensex, wholesale price index (WPI), and index of industrial production (IIP) as a proxy of gross domestic product, interest rates, Indian rupee - U.S. dollar exchange rate, and gold reserves of the country. Using the monthly data from April 1995 – March 2018, the relationship was explored empirically by using the autoregressive distributed lag model and error correction model. The ARDL results suggested that the long run cointegration between the prices of gold and the macroeconomic variables during the period of the study and gold reserves of RBI, BSE Sensex, WPI, exchange rate, and IIP were found to be significantly affecting the gold prices. However, interest rates were found to be statistically insignificant during the period of the study. The error correction term, which was negative and highly significant, confirmed the convergence to the long run equilibrium. The results of this study have important implications for the Indian economy and will be helpful for policy formulation.